Effect of Superplasticizer and Wetting Agent on Volumetric and Mechanical Properties of Cold Recycled Mixture with Asphalt Emulsion - Wenting Yang; Jian Ouyang; Yan Meng; Taixiong Tang; Jijiang Chen; Baoguo Han (Advances in Materials Science and Engineering)
Cold recycled mixture with asphalt emulsion (CRME) has gained more appreciation due to its environmental and economical advantages. Surfactant greatly affects the interaction between asphalt emulsion and cement, which can greatly affect the volumetric and mechanical properties of CRME. If the surfactant can greatly improve the volumetric and mechanical properties of CRME, that could be of great attraction. In this study, a polycarboxylate-based superplasticizer and wetting agent (DN500, polymers containing high-pigment groups) were employed to improve the volumetric and mechanical properties of CRME. Results indicate that the addition of superplasticizer and DN500 can reduce the void content of CRME and increase the indirect tensile strength (ITS) and stiffness modulus as well as critical strain energy density (CSED) of CRME. Besides, the failure strain of CRME is also increased by adding superplasticizer and DN500. This phenomenon is probably due to that superplasticizer can decrease the viscosity of cement asphalt emulsion paste (CAEP) and help to form a better asphalt film, and DN500 can moderately decrease the viscosity of CAEP and increase the wetting ability of asphalt emulsion as a wetting agent. CRME with superplasticizer has the best mechanical properties among all CRMEs. Compared to reference CRME, the ITS, stiffness modulus, and CSED of CRME with superplasticizer can increase by 33.7%, 8.0%, and 17.5% at the optimum water content, respectively. It is recommended to improve the volumetric and mechanical properties of CRME by adding superplasticizer.